Why don’t oil shocks cause inflation? Evidence from disaggregate inflation data - Bachmeier, Lance J.; Cha, Inkyung (My University, 2011)
This paper uses disaggregate U.S. inflation data to evaluate explanations for the breakdown of the relationship between oil price shocks and consumer price inflation. A data set with measures of inflation, energy intensity, labor intensity, and sensitivity to monetary policy is constructed for 97 sectors that make up core CPI inflation. A comparison of the 1973–85 and 1986–2006 time periods reveals that substitution away from energy use in production and monetary policy were both important, with approximately two-thirds of the change in response of inflation to oil shocks being due to reduced energy usage, and one-third to monetary policy. We find no evidence that other factors, such as changes in wage rigidities or changes in the persistence of oil shocks, played a role.
Keywords: Inflation; Price; Oil shock; Energy intensity; Monetary policy; Labor intensity; Disaggregate; Great Inflation